Treatment of T2DM-related inflammation and vascular injury by regulating cellular crosstalk in the islet microenvironment - Sun, Aru; Yang, Haoyu; Sun, Jun; Luo, Jinli; Zhou, Ling; Bao, Tingting; Tong, Xiaolin; Lin, Yiqun; Han, Lin (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus (T2DM), a complex systemic metabolic disorder caused by multiple factors, has been linked to numerous acute and chronic complications. T2DM pathogenesis includes glucotoxicity, lipotoxicity, inflammatory cytokines, and amyloid formation. Within the pancreatic islet microenvironment, the crosstalk among cell types plays a significant role in these pathogenic mechanisms. Islet β cells, macrophages, and endothelial cells, the three primary cell types, engage in intercellular communication under physiological and pathological conditions, critical to maintaining islet homeostasis and promoting the pathological progression of T2DM. This review discusses the interactions between these islet cells, particularly how their crosstalk affects islet function and T2DM development. Additionally, natural products targeting islet cell interactions are discussed as a therapeutic approach for T2DM, along with other personalized treatment options, including exosomes, parasitic therapy, and dietary interventions. Emerging strategies that regulate intercellular signaling and complex crosstalk within the islet microenvironment offer promising avenues for T2DM treatment.